Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's start by understanding the given vectors:
- [tex]\(\overrightarrow{O A} = 11x + 6y\)[/tex]
- [tex]\(\overrightarrow{O B} = 4x + 10y\)[/tex]
- [tex]\(\overrightarrow{C O} = -13x + 11y\)[/tex]
We need to find the following vectors:
a) [tex]\(\overrightarrow{B A}\)[/tex]:
The vector [tex]\(\overrightarrow{B A}\)[/tex] is obtained by subtracting vector [tex]\(\overrightarrow{O B}\)[/tex] from [tex]\(\overrightarrow{O A}\)[/tex]:
[tex]\[ \overrightarrow{B A} = \overrightarrow{O A} - \overrightarrow{O B} \][/tex]
Substitute the given vectors:
[tex]\[ \overrightarrow{B A} = (11x + 6y) - (4x + 10y) \][/tex]
Simplify by combining like terms:
[tex]\[ \overrightarrow{B A} = 11x + 6y - 4x - 10y \][/tex]
[tex]\[ \overrightarrow{B A} = (11x - 4x) + (6y - 10y) \][/tex]
[tex]\[ \overrightarrow{B A} = 7x - 4y \][/tex]
So, [tex]\(\overrightarrow{B A} = 7x - 4y\)[/tex].
b) [tex]\(\overrightarrow{A C}\)[/tex]:
The vector [tex]\(\overrightarrow{A C}\)[/tex] is obtained by subtracting vector [tex]\(\overrightarrow{O A}\)[/tex] from [tex]\(\overrightarrow{C O}\)[/tex]. Note that [tex]\(\overrightarrow{C O}\)[/tex] points from [tex]\(C\)[/tex] to [tex]\(O\)[/tex], but we need [tex]\(\overrightarrow{O C}\)[/tex], which is the negative of [tex]\(\overrightarrow{C O}\)[/tex]:
[tex]\[ \overrightarrow{O C} = -\overrightarrow{C O} = -(-13x + 11y) = 13x - 11y \][/tex]
Now, we can find [tex]\(\overrightarrow{A C}\)[/tex] by:
[tex]\[ \overrightarrow{A C} = \overrightarrow{O C} - \overrightarrow{O A} \][/tex]
Substitute the given vectors:
[tex]\[ \overrightarrow{A C} = (13x - 11y) - (11x + 6y) \][/tex]
Simplify by combining like terms:
[tex]\[ \overrightarrow{A C} = 13x - 11y - 11x - 6y \][/tex]
[tex]\[ \overrightarrow{A C} = (13x - 11x) + (-11y - 6y) \][/tex]
[tex]\[ \overrightarrow{A C} = 2x - 17y \][/tex]
So, [tex]\(\overrightarrow{A C} = 2x - 17y\)[/tex].
Hence, the vectors are:
[tex]\[ \overrightarrow{B A} = 7x - 4y \quad \text{and} \quad \overrightarrow{A C} = 2x - 17y \][/tex]
- [tex]\(\overrightarrow{O A} = 11x + 6y\)[/tex]
- [tex]\(\overrightarrow{O B} = 4x + 10y\)[/tex]
- [tex]\(\overrightarrow{C O} = -13x + 11y\)[/tex]
We need to find the following vectors:
a) [tex]\(\overrightarrow{B A}\)[/tex]:
The vector [tex]\(\overrightarrow{B A}\)[/tex] is obtained by subtracting vector [tex]\(\overrightarrow{O B}\)[/tex] from [tex]\(\overrightarrow{O A}\)[/tex]:
[tex]\[ \overrightarrow{B A} = \overrightarrow{O A} - \overrightarrow{O B} \][/tex]
Substitute the given vectors:
[tex]\[ \overrightarrow{B A} = (11x + 6y) - (4x + 10y) \][/tex]
Simplify by combining like terms:
[tex]\[ \overrightarrow{B A} = 11x + 6y - 4x - 10y \][/tex]
[tex]\[ \overrightarrow{B A} = (11x - 4x) + (6y - 10y) \][/tex]
[tex]\[ \overrightarrow{B A} = 7x - 4y \][/tex]
So, [tex]\(\overrightarrow{B A} = 7x - 4y\)[/tex].
b) [tex]\(\overrightarrow{A C}\)[/tex]:
The vector [tex]\(\overrightarrow{A C}\)[/tex] is obtained by subtracting vector [tex]\(\overrightarrow{O A}\)[/tex] from [tex]\(\overrightarrow{C O}\)[/tex]. Note that [tex]\(\overrightarrow{C O}\)[/tex] points from [tex]\(C\)[/tex] to [tex]\(O\)[/tex], but we need [tex]\(\overrightarrow{O C}\)[/tex], which is the negative of [tex]\(\overrightarrow{C O}\)[/tex]:
[tex]\[ \overrightarrow{O C} = -\overrightarrow{C O} = -(-13x + 11y) = 13x - 11y \][/tex]
Now, we can find [tex]\(\overrightarrow{A C}\)[/tex] by:
[tex]\[ \overrightarrow{A C} = \overrightarrow{O C} - \overrightarrow{O A} \][/tex]
Substitute the given vectors:
[tex]\[ \overrightarrow{A C} = (13x - 11y) - (11x + 6y) \][/tex]
Simplify by combining like terms:
[tex]\[ \overrightarrow{A C} = 13x - 11y - 11x - 6y \][/tex]
[tex]\[ \overrightarrow{A C} = (13x - 11x) + (-11y - 6y) \][/tex]
[tex]\[ \overrightarrow{A C} = 2x - 17y \][/tex]
So, [tex]\(\overrightarrow{A C} = 2x - 17y\)[/tex].
Hence, the vectors are:
[tex]\[ \overrightarrow{B A} = 7x - 4y \quad \text{and} \quad \overrightarrow{A C} = 2x - 17y \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.